Triple Helix Synergy for Development and Enhancing Competitiveness of SMEs - Herdiana Dyah Susanti; Dian Arief Pradana; Robit Nurul Jamil (Britain International for Academic Research (BIAR) Publisher, 2020)
Micro, small, and medium enterprises (SMEs) is the work done by individuals in the form of economic enterprises that meet the criteria of SMEs as set out in(Act No. 20 of 2008, 2008)about SMEs. The human factor is the most important factor in the development of SMEs to improve product quality and improve the welfare of the community. The triple helix is an innovative model of students, researchers, and policymakers to improve the university's role in improving the economic and social development, improve the role of governments to develop innovation, enhance enterprise collaboration with governments and universities to boost innovation. This study aims to (1) show the relationship triple helix in the development of the competitiveness of SMEs. (2) The effectiveness of the application of triple helix in the development of the competitiveness of SMEs. This study is quasi experimental research with pretest-posttest results of the application of triple helix on SMEs in Banyuwangi.